PENGARUH PENDIDIKAN KEWIRAUSAHAAN, DAN KREATIVITAS TERHADAP INTENSI BERWIRAUSAHA MELALUI ENTERPRENUER SELF EFFICACY - Dharma Satria, Novian; Trisnawati, Novi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the influence of entrepreneurship education and creativity on entrepreneurial intention through entrepreneurial self-efficacy as a mediating variable. This research employed a quantitative associative approach. The population consisted of Office Administration Education students of Universitas Negeri Surabaya, Class of 2023, who had completed entrepreneurship courses. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS. The results indicate that entrepreneurship education and creativity have positive and significant effects on both entrepreneurial self-efficacy and entrepreneurial intention. Furthermore, entrepreneurial self-efficacy positively and significantly affects entrepreneurial intention and mediates the relationship between entrepreneurship education, creativity, and entrepreneurial intention. Therefore, improving entrepreneurship education, creativity, and entrepreneurial self-efficacy can strengthen students' entrepreneurial intention.